Measuring the performance of mutual funds – a case study - Jakšić, Milena; Leković, Miljan; Milanović, Marina (Industrija, 2015)
In this paper we evaluate the performance of eight open-end mutual funds in the Republic of Serbia for the period 2009-2012, with the aim of testing the justification of active portfolio management of mutual funds, and determining the selection capability of Serbian portfolio managers. Risk-weighted returns of mutual funds are compared with the risk-weighted return of the leading Belgrade Stock Exchange index, Belex15, whereas the following are used as performance measures: Sharpe ratio ( ), Treynor ratio ( ), and Jensen’s or Alpha index ( ). The results suggest that the portfolio of Serbian mutual funds has inferior performance compared to the market portfolio, which indicates the lack of selection capabilities of domestic portfolio managers.